2019
DOI: 10.1002/2050-7038.12210
|View full text |Cite
|
Sign up to set email alerts
|

An improved hybrid PV‐wind power system with MPPT for water pumping applications

Abstract: SUMMARY This work articulates the hybrid photovoltaic‐wind power system development for water pump applications. The proposed control scheme is based on modified Artificial Bee Colony (ABC)‐based on Maximum Power Point Tracking (MPPT) algorithm.. On power circuit part, the single CUK converter‐fed induction motor driven a centrifugal pump and has been employed, which improves the system overall performance. The proposed MPPT control provides the smooth propagation of the motor operation as well as forces the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…20,21 In a WPS using an AC motor pump, the MPPT from solar PV and WECS is typically ensured by employing a dedicated power converter for power conditioning from either source and an additional converter to integrate power from these sources. 22,23 Such systems require more power devices resulting in increased losses and system cost. To overcome these drawbacks, few studies have proposed power processing of AC motor-based WPS using reduced converter count.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 In a WPS using an AC motor pump, the MPPT from solar PV and WECS is typically ensured by employing a dedicated power converter for power conditioning from either source and an additional converter to integrate power from these sources. 22,23 Such systems require more power devices resulting in increased losses and system cost. To overcome these drawbacks, few studies have proposed power processing of AC motor-based WPS using reduced converter count.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it is possible to extract the maximum power from both renewables using two power converters or multi‐input converter feeding a DC motor pump 20,21 . In a WPS using an AC motor pump, the MPPT from solar PV and WECS is typically ensured by employing a dedicated power converter for power conditioning from either source and an additional converter to integrate power from these sources 22,23 . Such systems require more power devices resulting in increased losses and system cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, climate dependency and high implementation cost are the major challenges of the present PV power system. The maximum power point tracking (MPPT) is essential for the achievement of maximum power point (MPP) because of non‐linear voltage/current characteristics as well as fast divergence of solar insolation level [3, 4]. For the efficient running of any PV‐based driven system, MPPT is an essential component.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of power generation level affected by climate leads to the difficulty of grid connection. [20][21][22] The equipment loss caused by the current from big to small will reduce product life. Nevertheless, in terms of the energy storage systems, the peak power supply of the grid can be adjusted.…”
Section: Introductionmentioning
confidence: 99%